PELATIHAN PEMBUATAN MATERI AJAR BERDIFERENSIASI MENGGUNAKAN CHATGPT BAGI GURU-GURU SMAN 2 TAPUNG HILIR - Asnawi, Asnawi; Mukhlis, Muhammad; Wahyuni, Sri; Dafit, Febrina (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
The design of differentiated teaching materials is the most important part for teachers in implementing current learning. Likewise, the use of technology in designing and implementing current learning is an inseparable part of learning. This is also needed by teachers of SMAN 2 Tapung Hilir in achieving future learning goals. Based on this, it is necessary to conduct training in creating differentiated teaching materials using Chat GPT for teachers of SMAN 2 Tapung Hilir. The target of this training partner is teachers of SMAN 2 Tapung Hilir. The training method used is guided and individual guided training. Based on the results of the training, it can be concluded that the mastery of teaching materials of teachers of SMAN 2 Tapung Hilir increased from 65% to 80%. The mastery of differentiated teaching material design of teachers of SMAN 2 Tapung Hilir increased from 70% to 80%. The mastery and use of ChatGPT of teachers of SMAN 2 Tapung Hilir increased from 60% to 80%. Teachers of SMAN 2 Tapung Hilir felt satisfied with the training on making differentiated teaching materials for teachers of SMAN 2 Tapung Hilir. Teachers of SMAN 2 Tapung Hilir felt that the material presented by the resource person in the training was very interesting and not boring for the training on making differentiated teaching materials for teachers of SMAN 2 Tapung Hilir. Teachers of SMAN 2 Tapung Hilir conveyed that the competence of the resource person in the training was very appropriate and of high quality for the training on making differentiated teaching materials for teachers of SMAN 2 Tapung Hilir.